Biotechnological valorization of oils from agro-industrial wastes to produce lipase using Aspergillus sp. from Amazon - Tacin, Mariana Vendrasco [UNESP]; Massi, Fernanda Pelisson; Fungaro, Maria Helena Pelegrinelli; Teixeira, Maria Francisca Simas; de Paula, Ariela Veloso [UNESP]; de Carvalho Santos-Ebinuma, Valéria [UNESP] (Elsevier, 2019)
Lipases are enzymes with a large number of applications at the industrial level. New producers and the development of bioprocess with high productivity are the major challenges of these enzymes industrially. Regarding the production process, oils from agro-industrial waste can emerge as efficient enzymes inductor reducing the production cost. Moreover, this process can minimize environmental problems related to agro-industrial disposal. Thus, this work proposes to evaluate a new Aspergillus specie from Amazon forest in Brazil as lipase producer using oils from agro-industrial waste (grape seed oil (GSO) and cotton seed oil (CSO)) as an inductor. It was used olive and soybean oil as standard. The microorganism metabolized all oils studied; however, the ones with a higher percentage of fatty acid esters (>80%), namely, soybean, olive, and GSO, promoted the highest lipase production. By comparing the activity of the lipase produced, GSO allowed an enzyme activity 2 fold higher than CSO. The enzyme produced using GSO was characterized and pre-purified by precipitation, showing an optimum pH of 7.5 and stability for pH between 7 and 7.5 values; an optimum temperature of 45 °C and a thermal stability between 30 and 50 °C was achieved. In conclusion, a new isolated from Amazon, Aspergillus sp., can produce lipase for industrial purpose using GSO. Moreover, other oils from agro-industrial waste with a high percentage of fatty acid esters can be used as an inductor for lipase production.
Keywords: Agro-industrial waste; Aspergillus; Biorefinery; Grape seed oil; Lipases; Submerged culture